Modelling and simulation of batch fermentation for lactobacillus plantarumby using Matlab® software - Mohamad Hud, Nornadira (2016)
Lactobacillus plantarum is being regarded as probiotics due to its usefulness mainly in treating gastrointestinal disease. An increase in awareness of having a good health among a citizen nowadays causes an increase in the demand of probiotics. Modelling and simulation is one of the evaluation tool in feasibility, designing and optimizing the complex process of simulation. The production of biomass, product and substrate concentration are predicted in this study. Varying kinetic parameters shows changes in a pattern of biomass, lactic acid and glucose concentration. Furthermore, maximum growth rate is found to be one of the kinetic parameter that gives a greatest influence in the batch fermentation of L. plantarum. Increasing the maximum growth rate tends to show a pattern of increasing biomass and lactic acid concentration which eventually lead to an optimisation of biomass production. In conclusion, maximum growth rate affects the batch fermentation of Lactobacillus plantarum.